Clinical Features and Risk of Relapse in Children and Adults with Myelin Oligodendrocyte Glycoprotein Antibody–Associated Disease. Issue 1 (15th October 2020) - Cobo‐Calvo, Alvaro; Ruiz, Anne; Rollot, Fabien; Arrambide, Georgina; Deschamps, Romain; Maillart, Elisabeth; Papeix, Caroline; Audoin, Bertrand; Lépine, Anne Fabienne; Maurey, Hélène; Zephir, Helene; Biotti, Damien; et al.
Abstract : Objective: The main objective was to compare clinical features, disease course, and myelin oligodendrocyte glycoprotein (MOG) antibody (Ab) dynamics between children and adults with MOG‐Ab–associated disease (MOGAD). Methods: This retrospective multicentric, national study included 98 children and 268 adults with MOGAD between January 2014 and September 2019. Cox regression model for recurrent time‐to‐event data and Kaplan–Meier curves for time to antibody negativity were performed for the objectives. Results: Isolated optic neuritis was the most frequent clinical presentation in both children (40.8%) and adults (55.9%, p = 0.013), and acute disseminated encephalomyelitis syndrome was more frequent in children (36.7% vs 5.6%, p  < 0.001). Compared to adults, children displayed better recovery (Expanded Disability Status Scale ≥ 3.0 at last follow‐up reached only by 10 of 97 [10.3%] vs 66/247 [26.7%], p  < 0.001). In the multivariate analysis, adults were at higher risk of relapse than children (hazard ratio = 1.41, 95% confidence interval [CI] = 1.12–1.78, p = 0.003). At 2 years, 64.2% (95% CI = 40.9–86.5) of nonrelapsing children became MOG‐Ab negative compared to 14.1% (95% CI = 4.7–38.3) of relapsing children (log‐rank p  < 0.001), with no differences observed in adults (log‐rank p = 0.280). Interpretation: MOGAD patients differ in the clinical presentation at onset, showing an age‐related shift in the clinical features across age groups. Compared to children, adults have a higher risk of relapse and worse functional recovery. Finally, children with monophasic disease become MOG‐Ab negative earlier than relapsing children, but this is not true in adults. Considering these differences, management and treatment guidelines should be considered independently in children and adults. ANN NEUROL 2021;89:30–41